PEMBERDAYAAN EKONOMI DESA MELALUI PEMBUATAN BRAND PERTANIAN SEBAGAI IDENTITAS PRODUK BERBASIS KEARIFAN LOKAL: - - Yusuf, Yusuf; Latifah, Eny (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Community empowerment with assistance in creating agricultural brands as a form of identity is one of the community service activities with the aim of creating village economic empowerment based on local wisdom. The method used is Participatory Action Research (PAR) where in our actions we involve the community so that it can be felt by the parties who do have a role in it. The result of the activity is the creation of a brand logo from agricultural commodities which will later become the identity of local products from Karangtawar Village, Laren District, Lamongan Regency. With the existence of agricultural product brands, it can be known that village products are typical and can be developed in order to improve the village economy to be introduced to domestic and international markets.